Aplikasi Mobile Augmented Reality untuk Media Edukasi Senjata Militer berbasis Application Programming Interface - Da Yuan, Ferdinansyah; Zakariyah, Muhammad (Institut Teknologi Garut, 2023)
Ownership of weapons throughout the world, especially firearms, is increasing sharply, giving rise to problems in terms of security and safety. The public must be aware of the risks and threats associated with the misuse of illegal weapons. That way, the public can have a better understanding of gun control and increase awareness of the dangers of violence and crime caused by weapons. The application that will be designed aims to apply Android-based Augmented Reality (AR) as a medium for military weapons education by getting to know various types of weapons and the dangers they pose by presenting more interesting and interactive information. The Augmented Reality (AR) method used in this application is the markerless and markerbase method. The markerless method does not require special markers to display virtual objects, making it possible for AR to be used anywhere. The markerbase method requires an image medium (marker) to display virtual objects by recognizing the position and orientation of the marker. Application Programming Interface (API) allows applications to communicate efficiently and easily with other applications via the Web Dashboard. By using API, it can be easy to update the content of military weapons information databases and quizzes automatically via an internet connection. In this research, the Multimedia Development Life Cycle (MDLC) approach was used as the method to be applied. By considering the results of testing that has been carried out through black box testing, angle testing, distance testing, and light intensity testing, it shows that the designed application can run well according to the expected goals, namely as an interactive educational medium that attracts various types of weapons and the dangers they cause. .